Factors Affecting Adoption of M – Wallets: Moderating Role of Financial Incentives - Mr. Sunil Kumar; Ms. Abha Gupta (Ramanujan International Journal of Business and Research, 2021)
This research has investigated the factors which has affected consumers attitude towards adoption of mobile wallet and furthermore it has explored that does attitude has any impact on consumers adoption towards mobile wallet? The study has evaluated the moderating effect of financial incentives between attitude and adoption of mobile wallet. The study uses the sample of 454 college going students, professionals and non professionals. Confirmatory factor analysis was done because the measurement tools wad adapted one. Further, Structural Equation Modeling was used to validate the relationship between different variables. Moderator was assessed using PROCESS Macro where financial incentives have taken as moderator. The result of the study highlights that first, there is a significant impact between perceived ease of use, perceived usefulness, subjective norms, trust and situational factors on attitude of consumers. Second, it was evident from the result of the study that attitude has significant impact on adoption of mobile wallet. Third, it was also found that financial incentives have significant moderating effect between attitude and adoption of mobile wallet. The study is done with a sample of 454 with two types of people first, college students, professionals and non professionals from Delhi -NCR Region only. The result of the study cannot be generalized in case of users belonging to other groups and places. The findings of the research suggest that as the number of people using smart phones are increasing, people are findings it easier to make payment through various mobile applications. These mobile apps can be customized keeping in mind the nature of users. Simplification of application and some visible incentives will definitely affect the attitude of people to use mobile wallet. Uses of wallet can be popularized among people in B and C grades cities also. The current study has contributed in the domain of financial transactions. The study has added two new variables i.e. situational factors and financial incentives. The result of the study suggests that situational factors have significant impact on attitude whereas financial incentives have moderating effect between attitude and adoption of mobile wallets.